2020
DOI: 10.1080/13880209.2020.1803370
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of total flavonoids from Alpinia officinarum rhizoma against ethanol-induced gastric ulcer in vivo and in vitro

Abstract: Context: Alpinia officinarum Hance (Zingiberaceae) is traditionally used to treat inflammation, pain, colds and digestive diseases. Objective: To investigate the potential protective mechanism of total flavonoids from the rhizomes of A. officinarum (F-AOH) in ethanol-induced acute gastric in vivo and in vitro. Materials and methods: In vivo: Gastric damage was induced in BALB/c mice by administering ethanol (10 mL/kg) after oral treatment with F-AOH at 126.8, 63.4 and 31.7 mg/kg or ranitidine (Ran) at 100 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 35 publications
5
19
0
Order By: Relevance
“…[10] As an HP, GLJ-XF was first recorded as Liangfu Wan in 'Liangfang Jiye' during the Qing dynasty (1700 AD) and has long been used for the treatment of colds, stomachache, and dyspepsia. [11] Modern pharmacological studies have shown that both GLJ and XF have protective effects on the gastric mucosa, [12,13] which is due to the rich volatile oils in the dried roots of these plant species. GLJ has been conventionally used for many conditions, such as for 'dispelling cold', relieving pain, 'warming the stomach', and as an antiemetic agent, [14] whereas XF possesses medicinal properties which include 'coursing the liver', resolving depression, 'regulating qi', and analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…[10] As an HP, GLJ-XF was first recorded as Liangfu Wan in 'Liangfang Jiye' during the Qing dynasty (1700 AD) and has long been used for the treatment of colds, stomachache, and dyspepsia. [11] Modern pharmacological studies have shown that both GLJ and XF have protective effects on the gastric mucosa, [12,13] which is due to the rich volatile oils in the dried roots of these plant species. GLJ has been conventionally used for many conditions, such as for 'dispelling cold', relieving pain, 'warming the stomach', and as an antiemetic agent, [14] whereas XF possesses medicinal properties which include 'coursing the liver', resolving depression, 'regulating qi', and analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric ulcers are still a global gastrointestinal disorder. Ethanol ingestion prompts intensified ulcer index, proven by marked gastric mucosal long hemorrhagic bands, petechial lesions with ulcerative inflammation [ 28 ], gastric degeneration and necrosis [ 29 ], death of epithelial cells, and local or multiple hemorrhagic ulcers [ 30 ]. This may be attributed to the high expression of various inflammatory cytokines and chemokine’s that are chemotactic to leukocytes and other cells of inflammatory processes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 According to the literature research, the efficiency of A. officinarum in treating gastritis and gastric cancer was closely related to the component of TFAO. 15 In this study, we established MFC tumor-bearing model and analyzed the effects of TFAO on the tumor growth, organ indices, and the concentrations of serum PCNA, MMP-9, VEGF, IL-6, IL-1β, and IL-17 in vivo. Additionally, in vitro experiments were carried out to determine the effects of galangin on the cellular proliferation of BGC-823 cells, cell cycle, apoptosis, and the activity of Caspases, as well as its effects on the expression of Caspase 3, Caspase 8, Caspase 9, CyclinB1, CyclinD1, Bcl-2, Bax, and STAT3 protein.…”
Section: Discussionmentioning
confidence: 99%